Long-Term Cardiac Morbidity and Mortality in Patients With Aortic Valve Disease Following Liver Transplantation: A Case Matching Study. (December 2017) - Nicolau-Raducu, Ramona; Marshall, Thomas; Patel, Hamang; Ural, Kelly; Koveleskie, Joseph; Smith, Susan; Ganier, Donald; Evans, Bryan; Fish, Brian; Daly, William; Cohen, Ari J.; Loss, George; et al.
Introduction. This retrospective study examined the role of aortic valve (AV) disease in patients who underwent orthotopic liver transplantation (OLT) to determine the incidence of postoperative cardiac morbidity and mortality when compared with a matched control group without AV disease. Methods. Patients were included in the AV group if diagnosed with aortic stenosis (AS) or aortic regurgitation or had received AV replacement prior to OLT. The AV group (n = 53) was matched to a control group (n = 212) with the following preoperative variables: type of organ transplanted, age, gender, race, body mass index, MELD, redo-transplantation, preoperative renal replacement therapy, nonalcoholic steatohepatitis, viral hepatitis, diabetes, and coronary artery disease. A 1:4 ratio was utilized to improve the efficiency and power of the analysis. Results. No significant difference in survival or posttransplant cardiac complications (acute coronary syndrome, heart failure, or dysrhythmia) was observed between groups. However, statistically significantly more patients—11% (6/53)—required coronary intervention following OLT in the AV group, whereas 3% (7/212) required coronary intervention (χ 2 = 5.8; P = .0156) in the control group. Following OLT, 9% (5/53) in the AV group required surgical or nonsurgical AV intervention, whereas no valvular events were observed in the control group. Event-free survival in the AV group, with an end point defined as AV intervention (n = 5) and death (n = 10), was 92% (49/53) at 1 year, 83% (44/53) at 3 years, and 72% (38/53) at 5 years. Conclusions. Patients with pretransplant AV replacement or AS have significant cardiac complications (myocardial infarction, AV replacement, or cardiac death) in 1 to 3 years post-OLT.